1995
DOI: 10.1021/jf00051a042
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Particle Sizes and Particle Size Distributions in Crystalline Fractionation of Lard

Abstract: Particle sizes and particle size distributions of lard in the process of multiple-step crystalline fractionation were studied by natural sedimentation spectrophotometry according to Stokes's law and Beers's law. The average particle size diameter and their distributions of lard fractions varied with the crystallization temperatures. Average particle size decreased significantly 0, < 0.05) with the crystallization vessel cooling rates (0.5, 1.0, and 2.0 "C min-l) and agitator speeds (50,100, and 150 rpm). Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…2d). Wang and Lin [5] also demonstrated that the mean size of crystals (as measured by spectrophotometry) decreases as the cooling rate increases. Herrera and Hartel [4] drew the same conclusions in a study on milk fat using polarized light microscopy.…”
Section: Comparative Study Of a Rapid Cooling Program And A Cooling Pmentioning
confidence: 95%
See 1 more Smart Citation
“…2d). Wang and Lin [5] also demonstrated that the mean size of crystals (as measured by spectrophotometry) decreases as the cooling rate increases. Herrera and Hartel [4] drew the same conclusions in a study on milk fat using polarized light microscopy.…”
Section: Comparative Study Of a Rapid Cooling Program And A Cooling Pmentioning
confidence: 95%
“…They have an impact on the nucleation rate [2], crystal number and size [3][4][5], crystalline polymorphism [6] and the nature of the crystallized triacylglycerols. During dry fractionation of these fats, cooling conditions affect the quality of the resulting fractions [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The cooling rate, and more directly the degree of supercooling, have a major impact on crystal morphology (number and size) (Wang and Lin [29]), fraction yield and quality (Deffense [5]; Deffense [30]). A higher degree of supercooling leads to the formation of a large number of nuclei and uncontrollable crystallisation, i.e.…”
Section: Description Of the Mechanisms Involved During Coolingmentioning
confidence: 99%
“…Firmness of lard was improved through blending with hydrogenated stock 2 or hard component isolated from fractional crystallization. In the past, the separation of hard component of lard stearin has been accomplished through techniques such as short-path distillation 8 , supercritical carbon dioxide extraction 9 , or dry and solvent crystallization 10,11 . Although stearin is the mainly targeted product, a fair proportion of the liquid component is also recovered as the co-product of fractionation.…”
Section: Introductionmentioning
confidence: 99%